Penerapan Metode TOPSIS untuk Penentuan Penerima BLT pada Pemerintah Desa Ciherang Pondok Bogor - Sismadi, Sismadi (Teknik Informatika Universitas Pamulang, 2021)
The Covid-19 pandemic condition with the implementation of PPKM had a broad impact on the economic sector on people's lives, especially residents of Ciherang pondok village, Bogor. This occurs with the limit of all local area exercises so it is hard for them to have the option to address essential issues to get by. Most of Ciherang Pondok locals are farmers, laborers, and freelancers, the percentage of workers who have a fixed income is very small. For this condition, the village government provides cash social assistance. To be able to distribute the aid in a targeted manner,Â was difficult so that the assistance distributed was not in accordance with the target of residents who should have received assistance but did not receive assistance from the village or vice versa. To overcome these obstacles, the TOPSIS method was applied as a decision support tool to sort out residents who were entitled and not entitled to cash social assistance from the Ciherang pondok village government by applying several criteria, including occupation, number of dependents, income, and homeownership. The total recipients of the temporary social assistance were 2800 people and the data processed by the TOPSIS method were taken as many as 234 people. The results of the sample who are entitled to receive as many as 172 people and are not entitled to 62. The parameter values generated from the TOPSIS method are entitled to receive 0.5 to 1 and are not entitled to receive below 0.5. the higher the parameter value, the more feasible it is to provide assistance. The eventual outcome is as a choice emotionally supportive network application to decide residents who are entitled to social assistance from the village government of Ciherang Pondok, Caringin Bogor.